The Influence of Organizational Culture and Compensation on Employee Performance through Work Discipline at PT. Bima Palma Nugraha - Edy Eri Iryanto; Mokh Natsir; Tanto G Sumarsono (Innovation Business Management and Accounting Journal, 2025)
The purpose of this study is to determine how organizational culture and compensation at PT. Bima Palma Nugraha affect employee performance through work discipline. to determine how organizational culture and work discipline affect employee performance, how compensation and work discipline affect employee performance, and how work discipline affects employee performance. With a sample size of 70 respondents, a descriptive method with proportional random sampling methodology was used. Regression equations and correlation coefficient analysis were used in data analysis to test the hypothesis. Based on the research findings, employee performance through work discipline is positively and significantly influenced by corporate culture and salary. Meanwhile, salary and work discipline have a positive and significant influence on employee performance, and work discipline has a beneficial influence on performance. This organizational culture will integrate individual diversity into shared values or norms among members and guide their behavior towards one goal: achieving consistently higher performance to advance the company.